Towards Highly Efficient Polymer Fiber Laser Sources for Integrated Photonic Sensors - Simon Spelthann; Stefanie Unland; Jonas Thiem; Florian Jakobs; Jana Kielhorn; Pen Yiao Ang; Hans-Hermann Johannes; Dietmar Kracht; Joerg Neumann; Axel Ruehl; Wolfgang Kowalsky; Detlev Ristau (Sensors, 2020)
Lab-on-a-Chip (LoC) devices combining microfluidic analyte provision with integrated optical analysis are highly desirable for several applications in biological or medical sciences. While the microfluidic approach is already broadly addressed, some work needs to be done regarding the integrated optics, especially provision of highly integrable laser sources. Polymer optical fiber (POF) lasers represent an alignment-free, rugged, and flexible technology platform. Additionally, POFs are intrinsically compatible to polymer microfluidic devices. Home-made Rhodamine B (RB)-doped POFs were characterized with experimental and numerical parameter studies on their lasing potential. High output energies of 1.65 mJ, high slope efficiencies of <semantics> 56 % </semantics> , and <semantics> 50 % </semantics> -lifetimes of ≥900 k shots were extracted from RB:POFs. Furthermore, RB:POFs show broad spectral tunability over several tens of nanometers. A route to optimize polymer fiber lasers is revealed, providing functionality for a broad range of LoC devices. Spectral tunability, high efficiencies, and output energies enable a broad field of LoC applications.